A DISCOURSE ANALYSIS OF PRIMARY SCHOOL ENGLISH TEACHING ARGUMENTS - Mukarromah, Marwah; Nuruddin Hidayat, Didin; Alek, Alek (Journal of English Education and Linguistics, 2024)
This study delves into the complex and contentious debate over language policy in primary education, focusing on the inclusion of English language instruction. Using a discourse analysis approach, the study delves into multifaceted arguments and counterarguments related to adopting English as a primary language of instruction in early childhood education. A qualitative descriptive research design with content analysis and discourse analysis techniques is used in the methodology. A Content Analysis Worksheet and a Transcription Template are among the research tools used to analyze YouTube videos about the removal of English as a mandatory subject in Indonesian primary schools. Findings reveal a range of viewpoints among stakeholders, including educators, government officials, and citizens, with regional perspectives from Bali emphasizing the practical importance of English in a tourism-centric environment. The discussion highlights the importance of clear communication, consideration of regional contexts, balancing academic requirements, and long-term planning in shaping effective language policies in primary education.